Gender Imbalance in Nigeria’s Legislature: A Peep into the 7th and 8th Assemblies - Obiwuru Chidera Rex (International Journal of Applied Business and International Management, 2019)
Marginalization of women in politics is very apparent most especially in Africa, where women are deemed by many as having no business with politics. In Nigeria, the above statement is also a fact when one considers the number of female parliamentarians in the country’s National Assembly. Ever since Nigeria returned to democracy in 1999, there have not been a substantial number of women in the legislature when compared to the number of their male counterparts. In the 7th and the 8th assemblies the problem still persisted. Howbeit, there are several factors responsible for this issue and these factors are what this study tries to look at. But before that, this paper looks briefly at the 7th and the 8th assemblies. To achieve the above however, secondary data is purely used.